Standardisasi Ekstrak Batang Greges Otot (Equisentum Debile Roxb.) - Ermawati, Nur (Universitas Pekalongan, 2019)
Introduction, Equisentum debile Roxb. Has efficacy as an antidiarrheal, antihepatitis, rheumatism, inflammation of the eyes, and hemorrhoids. Objective,the purpose of this study was to standardize the stem of Equisentum debile Roxb. extract. Method, standardization of extracts is carried out with specific parameters consisting of: organoleptic; thin layer chromatography (TLC), and non-specific parameters consisting of: water content; specific gravity; and microbial contamination (total plate count). Result, the stem of Equisentum debile Roxb extract has the characteristics of thick green extract, aromatic distinctive odor and bitter taste. Based on chemical test shows that the positive extract contains flavonoids, alkaloids and saponins. Specific weight, water content and total microbial contamination of stems of Equisentum debile Roxb were 0.890 g / ml, 10%, 1 × 104, respectively. Conclusion, the stem of Equisentum debile Roxb extracts have not met the overall standardization requirements.Keywords : The stem of Equisentum debile Roxb extracts, Standardization, specific parameters, non-specific parameters